2023
DOI: 10.20944/preprints202301.0460.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 mRNA Vaccines: From Inflammation to Hyperinflammation

Abstract: Each injection of any known vaccine results in a strong expression of pro-inflammatory cytokines. This is the result of the innate immune system activation, without which no adaptive response to the injection of vaccines is possible. COVID-19 mRNA vaccines would not escape this rule. Unfortunately, the degree of inflammation produced by these vaccines is variable, probably depending on the genetic background and previous immune experiences, which through epigenetic modifications, could have made the innate imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 179 publications
(252 reference statements)
0
1
0
Order By: Relevance
“…11,71 Regarding the cardiological complications, Giannota et al analyzed the role of oxidative stress in relation to the angiotensin/aldosterone hormonal axis which becomes upregulated by the circulating mRNA-expressed spike protein. 73 Cases of pericarditis, associated with increased oxidative stress, can be attributed to the SARS-CoV-2 spike protein expressed by mRNA vaccination. 11 In relation to oxidative stress, Table 2 provides a collection of representative studies, found by searching thoroughly in PubMed and ScienceDirect databases, that relate to post-COVID and mRNA injury syndromes.…”
Section: Lutein Oxidative Stress Post-covid Syndrome and Mrna Vaccina...mentioning
confidence: 99%
“…11,71 Regarding the cardiological complications, Giannota et al analyzed the role of oxidative stress in relation to the angiotensin/aldosterone hormonal axis which becomes upregulated by the circulating mRNA-expressed spike protein. 73 Cases of pericarditis, associated with increased oxidative stress, can be attributed to the SARS-CoV-2 spike protein expressed by mRNA vaccination. 11 In relation to oxidative stress, Table 2 provides a collection of representative studies, found by searching thoroughly in PubMed and ScienceDirect databases, that relate to post-COVID and mRNA injury syndromes.…”
Section: Lutein Oxidative Stress Post-covid Syndrome and Mrna Vaccina...mentioning
confidence: 99%